An analysis of innovations in business models: the case of Medlife’s sustainability report - Miruna Iuliana Cunea (Journal of Research and Innovation for Sustainable Society)
This study examines how innovation within business models in the healthcare sector is reflected in sustainability reporting, particularly focusing on the impact of recent crises, including the SARS-CoV-2 pandemic. This research focuses on Medlife S.A., a public listed Romanian healthcare company, and on its first sustainability report issued in 2023, covering its 2022 performance. The report highlights the group’s efforts to implement a sustainable business model during the pandemic, addressing key challenges such as innovation, digitalisation and environmental sustainability. The findings reveal that the innovation is emphasized through research conducted to combat the SARS-CoV-2 virus and through the adoption of digital technologies including telemedicine and robotic surgery. However, gaps remain in the use of emerging technologies such as artificial intelligence, blockchain, cloud computing, and the Internet of Medical Things (IoMT), which could further enhance sustainability efforts. This study contributes to the literature by providing insights into how business model innovation and sustainability reporting are interconnected during periods of crisis, emphasizing the need for healthcare companies to adopt emerging technologies to improve sustainability outcomes.